Pendidikan Islam Tradisional Dan Modern - Huda, Denis Ridho Nur; Rifa'i, Aulia Niswa Rifa’i; Nindiasari, Della Nindiasari; pratama, Dani Fajar Nurin Pratama; Khoiriyah, Asyan Hidayatul Khoiriyah (Al-Riwayah : Jurnal Kependidikan, 2023)
Education is a process of changing a person's attitude or behavior to mature humans through efforts to implement teaching by adhering to norms that have long been passed down from generation to generation. As for Islamic education, it should be able to change itself, not only by prioritizing religious knowledge, but Islamic education should also be able to answer the challenges of the times. Islamic education develops along with the emergence of Islam itself. Traditional and modern forms of education certainly have very significant differences. In this era, of course, the concept of education must be relevant to the conditions needed by society. Collaborative forms between traditional education and modern education are the right answer to face the present and future education systems.